2016
DOI: 10.1007/s00438-016-1187-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of DNA methyltransferase and demethylase genes in Fragaria vesca

Abstract: DNA methylation is an epigenetic modification essential for gene regulations in plants, but understanding on how it is involved in fruit development, especially in non-climacteric fleshy fruit, is limited. The diploid woodland strawberry (Fragaria vesca) is an important model for non-climacteric fruit crops. In this study, we identified DNA methyltransferase genes and demethylase genes in Fragaria vesca and other angiosperm species. In accordance with previous studies, our phylogenetic analyses of those DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…qPCR showed that, in the receptacle, expression of some of the SET methyltransferase genes peak at turning stage; an indication of a role for chromatin remodeling in strawberry fruit ripening. In addition, nine DNA methyltransferase genes and four demethylase genes were identified in the F. vesca genome 118 . These reports indicate that DNA methylation changes dramatically at the onset of ripening, warranting a detailed investigation of the roles of epigenomics in development and ripening in octoploid fruit.…”
Section: Fruit Developmentmentioning
confidence: 99%
“…qPCR showed that, in the receptacle, expression of some of the SET methyltransferase genes peak at turning stage; an indication of a role for chromatin remodeling in strawberry fruit ripening. In addition, nine DNA methyltransferase genes and four demethylase genes were identified in the F. vesca genome 118 . These reports indicate that DNA methylation changes dramatically at the onset of ripening, warranting a detailed investigation of the roles of epigenomics in development and ripening in octoploid fruit.…”
Section: Fruit Developmentmentioning
confidence: 99%
“…The quantitative reverse transcriptionpolymerase chain reaction (qRT-PCR) was carried out on a 7500 Real Time PCR system (Applied Biosystems, New York, USA), using a SYBR Premix Ex Taq (TaKaRa) reaction SYBR kit. The GADPH gene was used as a reference (Gu et al 2016). The primers used for qRT-PCR are listed in Supplemental Table S3.…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
“…derived from as many as four different diploid ancestors, which makes genetic studies very complicated (Shulaev et al 2011). Thus, the sequenced diploid woodland strawberry (Fragaria vesca) is emerging as a model for fruit crop plant species (Shulaev et al 2011;Gu et al 2016). In the present study, we performed a broad analysis of the LBD genes in the diploid woodland strawberry by investigating their chromosome position, evolutionary relationships, protein motifs, gene structure, cisacting elements, and expression profiles during callus formation and early fruit development.…”
mentioning
confidence: 95%
“…DNA methylation is a mitotically reversible and meiotically heritable epigenetic modification [17] that is important in plant growth and development [18][19][20]. Recent studies have shown that DNA methylation is associated with fruit development and ripening [21][22][23][24][25][26]. Treatment with 5-azacytidine (5-azaC), a methyltransferase inhibitor, was shown to affect the development of tomato [27], strawberry [28], and Acca sellowiana [29] fruit by decreasing DNA methylation levels, resulting in an early ripening phenotype.…”
Section: Introductionmentioning
confidence: 99%